Skin Grafts for Successful Wound Closure - Gore, Madhuri (IntechOpen, 2022)
Wounds with full thickness or deep partial thickness skin loss require skin grafts to achieve closure and minimize functional and aesthetic effects of healing. This book presents a comprehensive overview of skin grafts for wound closure. Section I includes three chapters that discuss established methods of wound bed preparation as well as new agents and methods. Section II includes three chapters that provide basic information about skin grafts and grafting procedure techniques.